The Effect of Price and Location on Successful Business Sale Warung Nasi Soto Tebo (Tetap Tambo) in Brayan, Medan - Chandra, Stanley; Dedy Lazuardi (Outline Journal of Management and Accounting, 2023)
This study aims to determine the effect of Price and Location either partially or simultaneously on Successful Business sale Warung Nasi Soto Tebo (Tetap Tambo) in Brayan, Medan. This research uses descriptive and quantitative methods. The population in the research were all consumer on 2022 with unknown total. A total sample was 120 consumers with a tolerable error rate of 5%. The sampling technique with nonprobability sampling. Data were analyzed using the multiple linear regression analysis method which resulted in the Equation of Successful Business = 22,992 - 0,199 + 0,714 + e. The results showed that the Price partially had a negative and significant effect on the successful business sale Warung Nasi Soto Tebo, with a tcount > ttable, which was 3.207 > 1.9804 and with a significant level of 0.002 < 0.05. Location partially have positive and significant effect on the successful business sale Warung Nasi Soto Tebo, with tcount > ttable, namely 8.510 > 1.9804 and with a significant level of 0.000 < 0.05. Based on the results of simultaneous hypothesis testing, it is known that the results of the -F test show that the Price and Location variables simultaneously affect the Successful Business, with Fcount > Ftable, namely 64.403 > 3.07 and with a significant value of 0.000 < 0.05. The amount of R Square is 0.524 or 52.4%, which means that the Price and Location affect the successful Business by 52.4% and the remaining 47.6% is influenced by other factors not examined in this study.